Bias of the Entropy Estimator for Symmetric Bernoulli Measures and the Weak Metric - N. E. Timofeeva (Моделирование и анализ информационных систем, 2015)
We consider symmetric Bernoulli measures and new weak metrics and obtain a closed-form expression of the entropy estimator bias.